Deficiencies of course management systems: Do students care? - Hannafin, Robert D.; Ioannou, Andri (My University, 2008)
Course management systems (CMSs) support thousands of courses at colleges and universities worldwide, delivering fully online courses as well as supplementing traditional face-to-face instruction. While quite a few studies have focused on the numerous benefits and technological advantages of CMSs, there is a paucity of empirical work focused on user attitudes about the efficiency and ease of use of CMSs, and perceived usefulness of potential additional features. We developed an attitudinal scale to better define and quantify these constructs. We piloted the survey with 234 college students who used WebCT Vista as a supplement to a face-to-face course. In this article we describe the development and initial validation of the scale. Since there is so little empirical work in this area, validating the instrument and identifying attitude factors should contribute to future research in this fast-growing arena. We further discus findings from our quantitative and qualitative data that provide evidence that CMSs are still evolving tools, and need accommodations and improvements.
Keywords: Online courses; Computer assisted instruction; Educational innovations; Universities & colleges